Effectiveness of E-Learning for University Students: Evidence from Bangladesh - Ali, Mohammad; Hossain, S.M Khaled; Ahmed, Tania (Asian Journal of Empirical Research, 2018)
The aim of current study is to analyse the effectiveness of e-learning for the students at university level. Data have been collected through questionnaire and it was given to 700 students. The questionnaire was returned by 667 students and 94.9% of them are using different e-learning tools, techniques or platforms. Eight variables have been used to measure the effectiveness of e-learning. Cronbach’s alpha test is used to measure the reliability and internal consistency of the associated factors. The exploratory factor analysis is used to extract the variables and to measure the factors loading in the study. One sample t-test has been performed to test the hypotheses. The outcome of the study supports that e-learning is faster, time and cost friendly, appropriate to work independently, add value to the learning of the students, usable for the purpose of active learning, faster, quick response, applicable outside the class room and quality of e-learning is satisfactory which indicates e-learning is effective.